2017
DOI: 10.1371/journal.pone.0187021
|View full text |Cite
|
Sign up to set email alerts
|

Alleviatory effects of silicon on the foliar micromorphology and anatomy of rice (Oryza sativa L.) seedlings under simulated acid rain

Abstract: Silicon (Si) is a macroelement in plants. The biological effects and mitigation mechanisms of silicon under environmental stress have become hot topics. The main objectives of this study were to elucidate the roles of Si in alleviating the effects on the phenotype, micromorphology and anatomy of the leaves of rice seedlings under acid rain stress. The results indicated that the combined or single effects of Si and simulated acid rain (SAR) stress on rice roots depended on the concentration of Si and the intens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Extract of leaves was then subjected to HPLC on Agilent Zorbax Eclipse XDB-C18 column (250 × 4.6 mm, 5 μm). TEM images of mesophyll cells were obtained (FEI Tecnai Spirit) according to Ju et al [39].…”
Section: Measurement Of Growth Indices Ros Iaa and Temmentioning
confidence: 99%
“…Extract of leaves was then subjected to HPLC on Agilent Zorbax Eclipse XDB-C18 column (250 × 4.6 mm, 5 μm). TEM images of mesophyll cells were obtained (FEI Tecnai Spirit) according to Ju et al [39].…”
Section: Measurement Of Growth Indices Ros Iaa and Temmentioning
confidence: 99%
“…At 50% of the WRC, there was not adjustment of polynomial models in both cultivars (Figure 1c and 1d). In rice (Oryza sativa L.) seedlings, 2 mM Si treatment increased the stomatal density and decreased the stomatal size of the adaxial epidermis (Ju et al, 2017). These same authors suggest that higher stomatal densities and smaller stomatal sizes improved the sensitivity of the stomatal regulation of the plants and improved the stomatal function at similar leaf areas.…”
Section: Resultsmentioning
confidence: 88%
“…Some studies focused on changes at the microscopic level of plants treated with Si. , In hemp leaves, Si action was noticeable in older leaves where a vascular tissue with wider xylem vessels was observed . The authors suggested that Si precipitates and strengthens xylem vessels by encrusting their cell walls.…”
Section: Resultsmentioning
confidence: 99%